Early Mobilization Therapy Robot for Medical Rehabilitation Purpose - Sutyasadi, Petrus; Parikesit, Elang; Widodo, Bernardinus Sri (Universitas Ahmad Dahlan, 2025)
Impairments in ambulation may result from neurological dysfunction. The expense of therapy constitutes a substantial obstacle to recovery following neurological disorders. An uncomplicated and cost-effective two-degree-of-freedom early mobilization trainer robot has been conceived and constructed. This device is intended for early training or adaptation before ready for mobilization training on the ground. The early mobilization trainer assists persons with mobility impairments during their early therapy phase. This research analyses the design and construction of an early mobilization trainer positioned within the patient's bed. The experimental findings indicate that in the condition with load at the hip joint, the output of this device can follow the trajectory input precisely. For the knee joint, the output of this device can follow the trajectory input, but with 0.9 degree of a steady-state error. This amount of steady state error does not affect the therapy because it is too small in term of knee movement precision during therapy.